A Comparative Study of the New Woman in Prissana, a Thai Novel by V. Na Pramuanmarg, and the New Woman in the English Novels at the End of the Nineteenth Century - Khunpakdee, Tapanat (Journal of Letters, 2020)
This research compares the characteristics of the New Woman with traditional female characters in educational, economic, social, and cultural contexts. The eponymous New Woman in Prissana by V. Na Pramuanmarg is compared with the New Women, Evadne, Angelica and Beth, in two English novels: The Heavenly Twins and The Beth Book by Sarah Grand. The research has found that Prissana’s character is completely different from traditional female characters because of her intelligence and education abroad, which cultivated her self-confidence and personal aptitudes. These qualities coincide with those of the English New Woman characters. The comparison shows that Prissana, Evadne, Angelica, and Beth are similarly intelligent and apt whether or not they have been formally educated. Socially, they aim for self-improvement and autonomy since they are as capable as men. On the economic level, they have either careers or other means of support resulting in financial stability. Meanwhile, they do not break cultural boundaries. The difference is that Prissana values marriage to a suitable partner, which explains why the novel concludes with Prissana marrying a perfect man whereas the English novels present both positive and negative sides of the New Woman’s marriage.